HUBUNGAN INTERAKSI SOSIAL DENGAN KUALITAS HIDUP LANSIA DI BPLU SENJA CERAH PROVINSI SULAWESI UTARA - Samper, Trisnawati P.; Pinontoan, Odi R; Katuuk, Mario (JURNAL KEPERAWATAN, 2017)
Abstract: Globally, the population of the elderly continue to rise. The increase of the number of elderly people is accompanied with a rise in health problems that are associated with the elderly. The degenerative process on the elderly causes the degeneration of the physical, psychological, and social conditions. One of the impacts of social change that is experienced by the elderly is the self-withdrawal of the elderly from their living environment. The purpose of the research is to analyze the association between social interaction and the quality of life of the elderly at BPLU Senja Cerah in North Sulawesi Province. The method of research is analytical descriptive with a cross-sectional design. The sample-taking technique in the research is purposive sampling with 32 samples. The collecting of data is done using a questionnaire. The processing of data uses the software computer with chi-square with the level of confidence interval of 95% (Î±=0,05). The results of the research shows the number of respondents with a good level of social interaction is 21 respondents, with 4 (12,5%) respondents having a sufficient quality of life, and 16 (50,0%) respondents with a high quality of life, while there are 12 respondents with a sufficient level of social interaction, where 9 (28,1%) respondents show a sufficient quality of life and 3 (9,4%) of respondents with a high quality of life and there is a p value of 0,004 < 0,05. This conclusion shows that there is a relationship between social interaction and the quality of life in the elderly. Keywords : Social Interaction, Quality of Life, Elderly Abstrak: Secara global populasi lansia terus mengalami peningkatan. Meningkatnya jumlah lansia tersebut diiringi dengan permasalahan kesehatan yang dihadapi. Proses degeneratif pada lansia menyebabkan terjadinya penurunan kondisi fisik, psikologis dan sosial. Salah satu dampak dari perubahan sosial yang sering dialami lansia adalah penarikan diri lansia disekitar lingkungan lansia tinggal. Tujuan penelitian ini untuk menganalisa hubungan interaksi sosial dan kualitas hidup lansia di BPLU Senja Cerah Provinsi Sulawesi Utara. Metode penelitian yang digunakan yaitu deskriptif analitik dengan rancangan cross sectional. Teknik pengambilan sampel pada penelitian yaitu purposive sampling dengan jumlah 32 sampel. Pengumpulan data dilakukan dengan menggunakan kuesioner. Pengolahan data menggunakan program software komputer dengan uji Chi-square dengan tingkat kemaknaan 95% (Î±=0,05). Hasil penelitian menunjukkan jumlah responden dengan interaksi sosial baik terdapat 21 responden dimana 4 (12,5%) responden kualitas hidup cukup, 16 (50,0%) responden kualitas hidup tinggi sedangkan responden dengan interaksi sosial cukup sebanyak 12 responden dimana 9 (28,1%) responden kualitas hidup cukup dan 3 (9,4%) responden kualitas hidup tinggi dan didapat nilai p value 0,004 < 0,05. Kesimpulan ini menunjukkan ada hubungan interaksi sosial dengan kualitas hidup lansia. Kata Kunci : Interaksi Sosial, Kualitas Hidup, Lansia